2017
DOI: 10.1515/aoa-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

The Hearing Threshold of Employees Exposed to Noise Generated by the Low-Frequency Ultrasonic Welding Devices

Abstract: The aim of the study was to assess the hearing threshold levels (HTLs) in employees exposed to noise generated by low-frequency ultrasonic technological equipment in comparison with the HTLs of workers exposed to audible noise at the similar A-weighted equivalent-continuous sound pressure level.The study includes measurements of ultrasonic and audible noise at workplaces and hearing tests, i.e. conventional pure-tone audiometry and extended high-frequency audiometry. The study group comprised 90 workers, aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…In fact, noise hazard studies and investigations by previous researchers were mostly done in the context of the employment sector [ 3 ]. It was found that most occupational sectors expose workers to noise levels above regulatory limits [ 3 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. This situation has caused stricter controls to be enforced to regulate noise exposure [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, noise hazard studies and investigations by previous researchers were mostly done in the context of the employment sector [ 3 ]. It was found that most occupational sectors expose workers to noise levels above regulatory limits [ 3 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. This situation has caused stricter controls to be enforced to regulate noise exposure [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apart from engine maintenance, work activities in this industry also include chassis repair, painting and metal fabrication work. Next, the metal manufacturing industry is also identified to expose workers to noise hazards [ 10 , 13 , 55 ]. Activities such as metal cutting, grinding, shearing and welding are known to produce high noise levels [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the general conclusion of that study was that age was the primary predictor, and noise and ultrasound exposure acted as secondary predictors of the hearing thresholds in the extended high frequency range. Dudarewicz et al [18] also observed worse HTLs within the extended high-frequency range among workers exposed to ultrasonic noise, but in comparison with workers exposed to audible noise (without ultrasonic components) at a similar A-weighted SPL. On the other hand, in the above-cited study conducted among dental clinicians working with ultrasonic scalers, in addition to the post-exposure reduction of OAEs, a significant temporary threshold shift in the standard PTA was observed [12].…”
Section: Hearing Examinationsmentioning
confidence: 93%
“…As mentioned in the beginning, for years the golden standard in the diagnosis of NIHL has been the standard PTA usually performed in the frequency range of 125 (250)-8000 Hz. However, since EHFA, DPOAE and TEOAE are believed to be useful for monitoring early signs of NIHL [9][10][11], thus, in the present study, being a continuation of the authors' previous investigations [18], the aforesaid hearing tests were applied together with the standard PTA for an assessment of hearing among ultrasonic device operators. Industrial applications of low-frequency ultrasound include various uses which differ not only in terms of operating frequency, but also spectral and temporal characteristics of generated noise.…”
Section: Questionnaire Surveymentioning
confidence: 99%
“…Activities, such as grinding, use of power tools, and heavy machinery, had exposed the workers to harmful doses of noise [11][12][13]. The risk is greater when performing welding activities where workers are exposed to the combining effect of ultrasonic and loud audible noises [14]. The second noisiest industry is the furniture industry [15][16][17].…”
Section: Introductionmentioning
confidence: 99%